(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This study identify the Social Representations of the last speakers of the Zoque Ayapaneco, indigenous language in Tabasco, Mexico, It is the high degree of disappearance. We worked with the last four speakers of this indigenous language in. It is a descriptive exploratory qualitative study. Life history and non participant observation were used. It was identified that the social representations is that they are assumed as responsible for the transmission of their language to the children of the community, so they teach. They assume a separation of parents, due to disinterest. It is suggested to strengthen ties with the community and institutions.